The effect of diet quality on the risk of developing gestational diabetes mellitus: A systematic review and meta-analysis - Gao, Xiaoxia; Zheng, Qingxiang; Jiang, Xiumin; Chen, Xiaoqian; Liao, Yanping; Pan, Yuqing (Frontiers in Public Health, 2023)
Objective: To examine the effect of diet quality on the risk of gestational diabetes mellitus. Methods: This review included cohort and case-control studies reporting an association between diet quality and gestational diabetes mellitus. We searched PubMed, Cochrane Library, Web of Science, Embase, PsycINFO, CINAHL Complete, Chinese Periodical Full-text Database, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, and China Wanfang Database for studies published from inception to November 18, 2022. The Newcastle-Ottawa Scale was used for quality assessment, and the overall quality of evidence was assessed using the GRADEpro GDT. Results: A total of 19 studies (15 cohort, 4 case-control) with 108,084 participants were included. We found that betterhigher diet quality before or during pregnancy reduced the risk of developing gestational diabetes mellitus, including a higher Mediterranean diet (OR:0.51; 95% CI:0.30–0.86), dietary approaches to stop hypertension (OR:0.66; 95% CI:0.44–0.97), Alternate Healthy Eating Index (OR:0.61; 95% CI:0.44–0.83), overall plant-based diet index (OR:0.57; 95% CI:0.41–0.78), and adherence to national dietary guidelines (OR:0.39; 95% CI:0.31–0.48). However, poorer diet quality increased the risk of gestational diabetes mellitus, including a higher dietary inflammatory index (OR:1.37; 95% CI:1.21–1.57) and overall low-carbohydrate diets (OR:1.41; 95% CI:1.22–1.64). After meta-regression, subgroup, and sensitivity analyses, the results remained statistically significant. Conclusions: Before and during pregnancy, higher diet quality reduced the risk of developing gestational diabetes mellitus, whereas poorer diet quality increased this risk. Keywords: diet quality; diet; gestational diabetes mellitus; pregnancy; prepregnancy